Multi-Period Consumption Decision under Conditions of Uncertainty - Levy, Haim (Management Science, 1976)
An investor is faced with several investment alternatives. Any investment plan induces a vector of consumption where the consumption in each period is a random variable. Obviously, the optimal vector of consumption is determined by the multi-period utility function. However, in most cases we have no information on the investor's preference, and hence we cannot choose the optimal consumption strategy. Assuming that the multi-period utility function is nondecreasing we establish a decision rule which divides the feasible set of consumption strategies into two sets: the “efficient set” and the “inefficient set.” Thus, in the second step each investor selects the optimal consumption strategy from the efficient set according to his preference.